Design of a Real-Time Adaptively Tuned Dynamic Vibration Absorber with a Variable Stiffness Property Using Magnetorheological Elastomer - Toshihiko Komatsuzaki; Yoshio Iwata (Shock and Vibration, 2015)
An elastomer composite with controllable stiffness, known as a magnetorheological elastomer (MRE), is used in a dynamic vibration absorber whose natural frequency is tuned adaptively to the disturbance frequency through the application of an external magnetic field. The field-dependent property test of the fabricated MRE sample shows that the stiffness changes by more than six times compared to the baseline property value at a 40% iron powder volume concentration. The MRE is then used to fabricate a frequency-tunable dynamic absorber for mitigating transient vibrations of a one-degree-of-freedom system. Investigations show that the proposed absorber outperforms a conventional passive-type absorber throughout the tunable frequency range.